El uso de tecnologías en las clases de E/LE por los profesores de las escuelas públicas de la ciudad de Abaetetuba-PA: dificultades y posible solución - FERREIRA, Ívina Kelly Costa (2021)
According to the analysis carried out in internships, it was observed that the use of technological resources is scarce in Spanish classes and, therefore, students are not encouraged to acquire more knowledge related to this discipline. Thus, the present work entitled “the use of technologies in E/LE classes by teachers of public schools in the city of Abaetetuba-PA: difficulties and possible solution” seeks to show with ownership the problems teachers face to insert Digital Information and Communication Technologies (TDIC's) in their educational context, along with information on how their use could improve Spanish classes. Subsequently, a possible solution to solve contextualized problems will be suggested. To carry out this work and obtain information, a qualitative exploratory investigation was carried out, that is, a questionnaire was used, which was answered by teachers from six (6) public schools in the city of Abaetetuba, located in the state of Pará. In addition to this, the present work had important contributions from authors such as: Vanessa Dantas Viera (2017); Naricléia Terezinha Faustino (2010); Antônio Marcos de Oliveira Candia (2010) and others. The perspective is that new forms and methods are inserted in the Spanish classes, so that the interest of the students sharpens and their knowledge has progress, so, the discipline will be considered as important for the training as the others, because, the The use of technologies makes the discipline and knowledge about it more and more profound.